Potential biodiversity map of darkling beetles (Tenebrionidae): environmental characterization, land-uses and analyses of protection areas in Southern Patagonia - Rosas, Yamina Micaela (2019)
Different methodologies had been developed for species management and conservation based on modelling of potential biodiversity at regional scales. However, most of these models were fitted for umbrella species (e.g. big mammals) rather than micro-fauna. Beetles should be included to improve conservation strategies due to their functional roles and vulnerability in arid environments. The maps of potential biodiversity (MPB) based on different potential habitat suitability (PHS) maps are useful to indicate high biodiversity areas. Firstly, we aim to elaborate a MPB of darkling beetles (Coleoptera: Tenebrionidae) based on 10 species PHS maps inhabiting Santa Cruz Province (Argentina). Then, we analysed the MPB an environmental gradients and land-use variables. We explored 41 potential variables to develop PHS maps. The MPB was included into a GIS project, and was analysed considering climatic and topographic variables, ecological areas and soil organic carbon (SOC) stock, also sheep density, desertification and protected area network. The modelled showed great variability in their habitat requirements (e.g. temperature), where marginality (PHS differs from the available conditions) and specialization (environmental condition range of PHS) determined three species groups. MPB increased from grasslands in the NE to shrublands in the SE, and was higher with SOC, sheep density and desertification degree. Protection areas included lower MPB for darkling beetles, where provincial reserves have a major conservation role compared with national parks. MPB allowed us to understand the potential trade-offs with the environment and human uses. This gave us a tool to development new strategies (e.g. land-sparing) for management and conservation.